Miskonsepsi Pengerjaan Operasi Deret Aritmatika Di PGMI-3 Di UIN Sumatera Utara - Putri Puspitasari; Rora Rizky Wandini (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
Misconceptions are discrepancies or misunderstandings in understanding arithmetic series with scientists' understanding of concepts or concepts that are in accordance with the rules of arithmetic series. Students often make discrepancies or misunderstandings in calculating terms of arithmetic series. The research aims to determine the difficulties of PGMI 3 UIN North Sumatra students, totaling 39 students, in solving problems regarding arithmetic series with the aim of presenting material about arithmetic series. Basic concepts of arithmetic series, including general formulas and their properties. The results of this research provide a better understanding of the misconceptions that often occur in working on arithmetic series operations, so that they can help PGMI 3 UIN North Sumatra students in working on arithmetic series operations more effectively and with more appropriate teaching methods for students.